2016
DOI: 10.1021/acsami.6b02744
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of an Organic p–n Heterojunction: C60 on Single-Crystal Pentacene

Abstract: Designing molecular p-n heterojunction structures, i.e., electron donor-acceptor contacts, is one of the central challenges for further development of organic electronic devices. In the present study, a well-defined p-n heterojunction of two representative molecular semiconductors, pentacene and C60, formed on the single-crystal surface of pentacene is precisely investigated in terms of its growth behavior and crystallographic structure. C60 assembles into a (111)-oriented face-centered-cubic crystal structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
70
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 50 publications
9
70
1
Order By: Relevance
“…On account of the formation of electronic bands and the associated delocalization of charge carriers, [1][2][3] reasonably high charge carrier mobility has been reported in devices of single crystalline organic semiconductors. Figure 2 insets show typical AFM images of the Pn-SC samples covered with 20 nm-thick C 60 overlayers grown at various substrate temperatures, i.e., 160, 300, and 370 K. C 60 forms grains on the Pn-SC surface in the case of RT (300 K) growth as reported previously, [23,31] and it was found that the lateral sizes and shapes of these grains vary depending on the growth temperature. Proportional increase of the inplane mean crystallite size of C 60 with the growth temperature suggests importance of surface diffusion processes of the C 60 molecules on the Pn-SC surface as a leading factor for determination of the heterojunction structures.…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…On account of the formation of electronic bands and the associated delocalization of charge carriers, [1][2][3] reasonably high charge carrier mobility has been reported in devices of single crystalline organic semiconductors. Figure 2 insets show typical AFM images of the Pn-SC samples covered with 20 nm-thick C 60 overlayers grown at various substrate temperatures, i.e., 160, 300, and 370 K. C 60 forms grains on the Pn-SC surface in the case of RT (300 K) growth as reported previously, [23,31] and it was found that the lateral sizes and shapes of these grains vary depending on the growth temperature. Proportional increase of the inplane mean crystallite size of C 60 with the growth temperature suggests importance of surface diffusion processes of the C 60 molecules on the Pn-SC surface as a leading factor for determination of the heterojunction structures.…”
Section: Introductionsupporting
confidence: 62%
“…Figure 4 shows the XRR data representing the C 60 (111) and Pn-SC(002) spots of 20 nm-thick C 60 overlayers grown at various temperatures. [31] The fringe structures as well as the main peak profile are more pronounced for the C 60 overlayers formed at 350 K, as shown in Figure 4c, suggesting further improvement of the crystallinity. At RT (Figure 4b), the C 60 (111) reflection (upward arrow) at the outof-plane scattering vector (q z ) of 0.770 nm −1 is accompanied by Laue fringes on both sides indicating good crystallinity and crystal orientation of the overlayers, as reported previously.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations